Effects of aerobic exercise and diet intervention on glycaemic control and liver fat content in men and women aged 50–65 years with prediabetes and non-alcoholic fatty liver disease: a multicentre, randomised controlled trial. (November 2016) - Cheng, Sulin; Ge, Jun; Zhao, Can; Wiklund, Petri; Le, Shenglong; Yang, Yifan; Ke, Dandan; Wu, Na; Tan, Xiao; Sun, Jianqin; Wang, Renwei; Shi, Yongyong; et al.
Abstract: Background: Prediabetes and non-alcoholic fatty liver disease precede development of type 2 diabetes; however, appropriate lifestyle interventions might help to prevent such progression. We aimed to test whether aerobic exercise training and a high-fibre diet can reduce hepatic fat content and increase insulin sensitivity in individuals with prediabetes and non-alcoholic fatty liver disease. Methods: We did a randomised controlled trial in seven clinics in Yangpu district, Shanghai, China. We recruited individuals aged 50–65 years with impaired fasting glucose (5·6–6·9 mmol/L) or impaired glucose tolerance (2 h glucose 7·8–11·0 mmol/L) and diagnosed non-alcoholic fatty liver disease. We randomly assigned (1:1:1:1) participants to receive aerobic exercise, diet intervention, aerobic exercise plus diet intervention, or no intervention (control group) for 8 months. A computer program was used to generate the block randomisation sequence (block size 20). Progressive aerobic exercise training (60–75% intensity) was given three to five times per week in 30–60 min sessions. The diet intervention aimed to include 40% carbohydrate with a fibre intake of 18–25 g per day. The primary outcomes were hepatic fat content (assessed by proton magnetic resonance spectroscopy [ 1 H MRS]) and insulin sensitivity (assessed by oral glucose tolerance test), analysed in the intention-to-treat population. We also examined participants' DNA samples for PNPLA3 genotypes. Ethics approval was granted by the Ethics Committee of Shanghai Institute of Nutrition (ref 2013-003), and all participants provided written informed consent. This trial is registered with the ISRCTN registry, number ISRCTN42622771. Findings: Between June 1 and Dec 25, 2013, we screened 603 individuals, of whom 115 were eligible and randomly assigned to the exercise group (n=29), diet group (n=28), exercise plus diet group (n=29), or control group (n=29). Mean change in hepatic fat content was −24·4% (95% CI −41·7 to 7·1) in the exercise group, −23·2% (−45·1 to −1·3) in the diet group, and −47·9% (−65·8 to −30·0) in the exercise plus diet group, and 20·9% (−4·4 to 46·2) in the control group (p=0·006, p=0·002, and p<0·0001, respectively, for all intervention groups compared with the control group). Among individuals who completed the intervention, hepatic fat content decreased to normal levels (<5·6%) in ten (44%) of 23 participants in the exercise plus diet group, three (14%) of 22 participants in the exercise group, and nine (41%) of 22 participants in the diet group. However, insulin sensitivity increased significantly in the exercise plus diet group only (14%; p<0·05). No difference was found in PNPLA3 genotypes (GG, GC, and CC) among the groups. Interpretation: Aerobic exercise training combined with high-fibre intake can help to reduce liver fat content and increase insulin sensitivity more effectively than either exercise or increased fibre intake alone in patients with prediabetes and non-alcoholic fatty liver disease. This combined intervention should be used to improve health in these patients. Moreover, identification of patients with high hepatic fat content with novel imaging techniques (such as 1 H MRS) has the potential to maximise patient benefit and minimise intervention costs. Funding: China State Sport General Administration (2013B040 and 2015B039) and Chinese Nature Science Foundation (NSFC 31571219).